2009
DOI: 10.1038/nature08067
|View full text |Cite
|
Sign up to set email alerts
|

Yurt, Coracle, Neurexin IV and the Na+,K+-ATPase form a novel group of epithelial polarity proteins

Abstract: The integrity of polarized epithelia is critical for development and human health. Many questions remain concerning the full complement and the function of the proteins that regulate cell polarity. Here we report that the Drosophila FERM proteins Yurt (Yrt) and Coracle (Cora) and the membrane proteins Neurexin IV (Nrx-IV) and Na(+),K(+)-ATPase are a new group of functionally cooperating epithelial polarity proteins. This 'Yrt/Cora group' promotes basolateral membrane stability and shows negative regulatory int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
200
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(222 citation statements)
references
References 46 publications
17
200
2
3
Order By: Relevance
“…However, it was recently shown that some SJ components have a role in a newly identified phase of Drosophila epithelial polarity that occurs between stages 11 and 13 (Laprise et al 2009). Because of redundancy between SJ components involved in this polarity phase and the SJ component yrt, SJ proteins required for polarity can be identified only in a yrt zygotic mutant background (Laprise et al 2009). For example, single zygotic mutations in either the SJ gene Atpa or yrt show normal apical localization of Crb at stage 12 (Figure 7,D and E).…”
Section: Resultsmentioning
confidence: 99%
“…However, it was recently shown that some SJ components have a role in a newly identified phase of Drosophila epithelial polarity that occurs between stages 11 and 13 (Laprise et al 2009). Because of redundancy between SJ components involved in this polarity phase and the SJ component yrt, SJ proteins required for polarity can be identified only in a yrt zygotic mutant background (Laprise et al 2009). For example, single zygotic mutations in either the SJ gene Atpa or yrt show normal apical localization of Crb at stage 12 (Figure 7,D and E).…”
Section: Resultsmentioning
confidence: 99%
“…The EPB4.1 protein family is involved in cellular morphogenesis, and EPB41L5 was particularly investigated in terms of apicobasal polarity establishment via interaction with CRUMBS in early development (35,36). Previous work demonstrated that EPB41L5 was required during early embryo gastrulation, which seemed to be partially a result of EPB41L5-dependent FA modulation and cell-cell contact establishment via cadherins (37).…”
Section: Discussionmentioning
confidence: 99%
“…De cette façon, nous avons établi l'existence d'une interaction génétique entre yurt et Atpa (codant la sous-unité alpha de la Na + , K + -ATPase) ainsi qu'entre yurt et Neurexin-IV [7]. Nos expériences d'interactions génétiques et la caractérisa-tion phénotypique des double mutants ont permis de mettre en lumière le rôle jusqu'alors insoupçonné de la Na + , K + -ATPase et de la Neurexine-IV dans la polarité épithéliale.…”
Section: Interactions Protéiques Coopératives Dans L'établissement Etunclassified
“…Nos expériences d'interactions génétiques et la caractérisa-tion phénotypique des double mutants ont permis de mettre en lumière le rôle jusqu'alors insoupçonné de la Na + , K + -ATPase et de la Neurexine-IV dans la polarité épithéliale. Par la suite, l'analyse des interactions génétiques du gène yurt a été étendue à des gènes encodant des protéines adaptatrices associées à la membrane basolatérale, ce qui a permis de démontrer que l'inactivation simultanée des gènes yurt et coracle entraîne une organisation apicale de la membrane plasmique au détriment du domaine basolatéral lors de l'organogenèse [7]. Ce phénotype est significativement aggravé lorsque les deux gènes sont inactivés simultanément plutôt qu'un seul de ces gènes, soit yurt, soit coracle.…”
Section: Interactions Protéiques Coopératives Dans L'établissement Etunclassified
See 1 more Smart Citation